Effects of Structured Physical Activity on Holistic Development of Elementary School Children: A Systematic Review Based on Physical Literacy Framework - Aris Iskandar; Joni Taufik Hidayat (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2026)
Elementary school years represent a critical period for establishing foundations of health, motor competence, and socio-emotional skills. Despite strong evidence supporting the multidimensional benefits of structured physical activity, sedentary lifestyles and excessive screen time among Indonesian children raise serious concerns. Objective: This systematic review aimed to synthesize contemporary empirical evidence regarding the impact of structured physical activity on the physical, cognitive, and psychosocial development of elementary school children through the Physical Literacy (PL) framework. Method: This review followed the PRISMA 2020 protocol across six electronic databases for studies published between January 2018 and July 2026. Inclusion criteria comprised experimental, quasi-experimental, or randomized controlled trial designs; populations aged 6–12 years; structured physical activity interventions; and reporting at least one outcome in physical, cognitive, or psychosocial domains. Methodological quality was assessed using the Mixed Methods Appraisal Tool (MMAT) version 2018. Results: Forty-two studies met the inclusion criteria. Large effect sizes for motor competence (Hedges' g = 0.69–1.53) and moderate effect sizes for executive function and academic achievement (d = 0.40–0.65) were drawn from previously published meta-analyses of individual intervention studies rather than computed de novo, as no meta-analysis was performed in this review. The included studies further reported positive associations with emotional regulation, self-esteem, and social skills. High heterogeneity indicated substantial variation in intervention design and implementation context. Conclusion: The included evidence, synthesized narratively and appraised using the MMAT, generally indicates positive associations between structured physical activity and holistic child development, with the strongest support for motor competence outcomes. Policy recommendations include adopting PL-based physical education curricula, strengthening teacher capacity, and revitalizing traditional games as culturally-relevant learning media.